Application of Problem Based Learning Model on the Study of Land and Sea Waters to Improve Students' Critical Thinking Skills - Nonda Andini, Reka; Putra, Alfyananda Kurnia; An, Sumin; Mu’tashimbillah, Muhammad (CV Bumi Spasial, 2024)
Critical thinking skills are needed in geography lessons because they are closely related to solving geospheric problems that occur in the environment around students. Critical thinking skills are low because learning tends to be one-way or teacher centered, using conventional methods. The purpose of the study was to improve students' critical thinking skills by applying the Problem Based Learning model in geography subjects. The research is a Classroom Action Research (PTK) with the subject of class X-F MAN 1 Malang students totaling 32 students. Data collection using a test totaling 6 description questions that are adjusted to the indicators of critical thinking. Analysis of research data using quantitative descriptive. The results showed an increase of 43% from pre-cycle to cycle I with an average of 72.19 and increased by 17% in cycle II with an average of 84.38. Thus, after the application of the PBL model in geography lessons there was an increase in students' critical thinking skills.